Gratitude intervention for the management of psychological distress in breast cancer survivors - Sanjiwani, Anak Agung Sri; Dewi, Ni Luh Putu Thrisna; Wati, Ni Made Nopita; Lisnawati, Ketut (Talenta Publisher, 2025)
Psychological distress in breast cancer survivors is related to the sequelae of the treatment and care process. Distress experienced includes emotional experiences related to multifactor and causes interference in overcoming the challenges of cancer, including physical symptoms and treatment. This study aims to determine the effect of providing gratitude intervention in the form of a gratitude diary/writing on psychological distress in breast cancer survivors. Twenty-two respondents were involved in this study, divided into a control group (n=11) and an experimental group (n=11). The method used in this study was a quantitative experimental one-group pre-post-test design. The results showed that gratitude diary/writing was significant in reducing psychological distress in breast cancer survivors (anxiety p=0.003; stress p=0.003; depression p=0.003). Gratitude diary conditions breast cancer survivors to actively remember the positive side and then reinterpret the life experiences experienced by increasing appreciation for the positive things that have happened. Keyword: breast cancer survivor, gratitude diary, psychological distress,